How Adaptive Governance Policies Work in Climate Change - Marzuq, Muhammad Fauzan; Haning, M. Thahir; Abdullah, Muh. Tang; Muttaqin, Muttaqin (IHSA Institute, 2024)
This research explores the concept of Adaptive Governance in addressing climate change impacts. Adaptive Governance is an approach that emphasizes flexibility, collaboration, and continuous learning to manage the dynamic and unpredictable nature of climate-related challenges. The study examines how integrating scientific knowledge, technological advancements, and policy frameworks enhances adaptive capacity and resilience. It highlights the importance of accurate data, effective interagency coordination, and inclusive policymaking that engages local communities and stakeholders. The research identifies key factors influencing the success and challenges of implementing Adaptive Governance, including resource availability, institutional capacity, and political dynamics. Through case studies and literature review, the study demonstrates that while Adaptive Governance presents a robust framework for climate adaptation, it requires ongoing evaluation and adjustment based on empirical evidence and stakeholder feedback. The findings suggest that Adaptive Governance can significantly improve responses to climate change by fostering a responsive and sustainable approach to environmental management